Rancang Bangun Game Edukasi Santri Quest Berbasis Unity 3D Sebagai Media Pembelajaran Interaktif Bagi Santri - Widya Safitri; Farihin Lazim; Firman Santoso (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
The development of digital technology has significantly influenced various sectors,including education. One form of technology utilization in education is the implementationof educational games as interactive learning media. Educational games can improvelearning motivation by combining entertainment and educational elements into a singleplatform. Salafiyah Syafiiyah Sukorejo Islamic Boarding School has various regulationsthat must be understood by students. However, the delivery of these regulations is stillmostly conducted through conventional methods, making it less attractive for today'sdigital generation. This study aims to design and develop a Unity 3D-based educational game called SantriQuest as an interactive learning medium for students. The research method used is Researchand Development (R&D), while the system development method adopts Rapid ApplicationDevelopment (RAD). The game was developed using Unity Engine and C# programminglanguage. In this game, players act as students who must overcome obstacles, avoidhazards, and answer educational quizzes related to Islamic jurisprudence and science toreach the Freedom Finish as the final objective.The results show that the game has been successfully implemented with features such asLoading Screen, Main Menu, Select Quiz, Select Hero, Hero Controller, hero characters,monster characters, and quiz-based educational gameplay. Based on Black Box Testing, allmajor features function according to system requirements. Santri Quest is expected tobecome an attractive learning medium that enhances students’ understanding ofeducational materials and boarding school regulations